COMPETENTION EFFECT, DICIPLINE AND MOTIVATION TO FUNCTIONAL OFFICE PEFORMANCE ON MINISTRY OF ENVIRONMENT AND FORESTRY IN SOUTH SUMATERA PROVINCE. - Afan Absori; M. Idris; Choiriyah Choiriyah (KOLEGIAL, 2019)
The purpose of this study was to examine the effect of competence, discipline and motivation on the performance of functional officials at the Ministry of Environment and Forestry in South Sumatra Province.The Research character is corelation with used sample response 104 peoples. Used three independent variable and one dependent variable, data collection technique with questionnaire and interview then direct observation in the field. As instrument research is used for validity test, reliability test, data normality test, heteroscedasticity test, and multicollinearity test. Analysis mode have to determination coefficient test, test F, and t test.The results of the research R square value of 0.466 means that the independent variable (X) has an effect on the dependent variable (Y) of 46.6%. The F value is 29,045> Ftable 2.69 and the sig value is 0.000 <0.05, so that competence, discipline and motivation together have a significant effect on the performance of functional officials in the Ministry of Environment and Forestry in South Sumatra Province. Partially competency has a significant effect on the performance of the tcount 2.563 > ttable 1.987 and sig 0.012 <0.05. Discipline has a significant effect on the performance of the tcount 2.576 > ttable 1.987 and sig 0.011<0.05. Motivation hasn’t a significant effect on the performance of the value of tcount1.946 < ttable 1.987 and sig 0.055>0.05. In the practical aspect this research is an input for functional officials and employee coaching materials for performance improvement. As academically it becomes a reference for further research.